(3aUd GdNWGH ajeG JfRdJ Hg YfGjI GdcQje GdhgGHs - (3HgGA GdOjf eMeO egOj GdUjGOj GdQaGYj GdMSjfj, GdQhGS , J (B1287 (3g` s
(3ChdgG (B:s
(3CeG HYO aGdYHO GdeJbdH Ydi HSGW GdcQe GdaGQT NOjg ai HGH YfGjI eajV GdfYe s
(3BNQgG (B:s
(3hdG Jbd Ef gPG GdXghQ jchf HYO ehJi hgfGdc eGPG jchf ef EQJHGWc Hi hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B191s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9298) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs